Mucho más que buena letra. Escritura, arte caligráfico y civilización en Montevideo durante el siglo XIX - Beretta García, Ernesto (Escritura e Imagen, 2008)
After the independence and along the XIX century, during the process of cultural change which the montevidean government tried to impose in Uruguay, writing and caligraphy were asigned a commitment which is analysed in this article. A modern country tried to be established through it. The european liberal and industrialized nations were taken as a model, overcoming the traditional way of life considered “barbarian”. Education and alphabetization were found to be a main tool by the civilizating project, which enabled the assimilation of the european culture as well as the local development of bureaucratic capitalist forms. If writing had a functional nature, caligraphy, extremely ornamented and derived from it was considered a symptom of a superior culture and refinement, and the works of well known expert penmen were used to show the level reached by the country in its route to civilization.